Paradigma Baru Dalam Museum Seni dan Budaya Jawa Ullen Sentalu - Amarena Nediari (Humaniora, 2011)
The existence of the museum building as  conservation collection of historic objects often give the impression that the museum is an ancient building, dark and disheveled. While the new paradigm in the management of the museum is a museum not only as a place to store historical objects, but need to present the collection in an attractive package so that visitors interested in coming back again to the museum. Museum of art and culture of Java Ullen Sentalu, in Kaliurang has provided a new insight to the culture, especially Javanese culture in the family palace of Yogyakarta and Solo Palace. The main attraction of this Sentalu Ullen is to deliver information about the historic collection from the family palace is presented as a whole, so that leaves a deep impression for visitors. This museum has given the world a new concept in museums in Indonesia, which certainly can be applied to other museums in Indonesia.